Convergent or divergent Europeanization? An analysis of higher education governance reforms in France and Italy. (March 2017) - Dobbins, Michael
This article comparatively examines the higher education reform pathways of France and Italy. Using a scheme of empirical indicators, I focus on the divergent and convergent developments in these two countries, which played a pioneering role in the Europeanization of higher education. While France has consistently moved closer to a market-oriented model, legacies of academic self-rule were initially strengthened in Italy, before recent reforms aimed to crack down on academic power abuses. To explain these policy pathways, I pursue a dual theoretical argument by linking institutional isomorphism with historical institutionalism. Points for practitioners: The article examines the changing structures of higher education management and administration in France and Italy. It focuses on the new roles attributed to the state, university leaders and external stakeholders, and addresses whether both systems have converged on a market-oriented paradigm. I explain how and why various new competitive steering instruments were introduced. The analysis should be of interest to both scholars and practitioners due to its focus on new power arrangements in quality assurance, university administration and research governance.